Overexpression of a Cytosolic Abiotic Stress Responsive Universal Stress Protein (SbUSP) Mitigates Salt and Osmotic Stress in Transgenic Tobacco Plants - Udawat, Pushpika; Jha, Rajesh K.; Sinha, Dinkar; Mishra, Avinash; Jha, Bhavanath (Frontiers in Plant Science, 2016)
The Universal Stress Protein (USP) is a ubiquitous protein and plays an indispensable role in plant abiotic stress tolerance. The genome of Salicornia brachiata contains two homologues of intron less SbUSP gene which encodes for salt and osmotic responsive universal stress protein. In vivo localization reveals that SbUSP is a membrane bound cytosolic protein. The role of the gene was functionally validated by developing transgenic tobacco and compared with control (wild type and vector control) plants under different abiotic stress condition. Transgenic lines (T1) exhibited higher chlorophyll, relative water, proline, total sugar, reducing sugar, free amino acids, polyphenol contents, osmotic potential, membrane stability and lower electrolyte leakage and lipid peroxidation (malondialdehyde content) under stress treatments than control (WT and VC) plants. Lower accumulation of H2O2 and O2- radicals was also detected in transgenic lines compared to control plants under stress conditions. Present study confers that overexpression of the SbUSP gene enhances plant growth, alleviates ROS buildup, maintains ion homeostasis and improves the physiological status of the plant under salt and osmotic stresses. Principal component analysis (PCA) exhibited a statistical distinction of plant response to salinity stress, and a significant response was observed for transgenic lines under stress, which provides stress endurance to the plant. A possible signaling role is proposed that some downstream genes may get activated by abiotic stress responsive cytosolic SbUSP, which leads to the protection of cell from oxidative damages. The study unveils that ectopic expression of the gene mitigates salt or osmotic stress by scavenging ROS and modulating the physiological process of the plant.